Best Practice Checklist for Management of a Swine Show for Youth - Chad Carr; Justin Crosswhite (EDIS, 2011)
The management team for a swine show for youth should have a plan to manage the facilities, pigs, and personnel in a way that allows the show to be as stress-free and educational as possible. This 3-page fact sheet includes a checklist of information about unloading pigs, the size of the show ring, and pig handling training so that show managers know how to prepare for their show. Written by Chad Carr and Justin Crosswhite, and published by the UF Department of Animal Science, December 2011.